Sheffield Hallam Staff Wellness service: Four-year follow-up of the impact on health indicators. (September 2016) - Flint, Stuart W; Scaife, Robert; Kesterton, Sue; Humphreys, Liam; Copeland, Robert; Crank, Helen; Breckon, Jeff; Maynard, Ian; Carter, Anouska
Aims: Alongside the increasing prevalence of chronic health conditions such as cardiovascular disease and diabetes has been an increase in interventions to reverse these ill-health trends. The aim of this study was to examine the longitudinal impact of the Sheffield Hallam University Staff Wellness Service on health indicators over a five-year period. Methods: The Sheffield Hallam Staff Wellness Service was advertised to university employees. Of 2651 employees who have attended the service, 427 respondents (male = 162, female = 265) aged 49.86 ± 12.26 years attended for five years (4 years follow-up). Each year, participants were assessed on a range of health measures (i.e. cardio-respiratory fitness, body mass index, blood pressure, total cholesterol, high-density lipoproteins, lung function and percentage body fat). Participants also received lifestyle advice (based on motivational interviewing) as part of the intervention to either improve, or in some cases maintain, their current health behaviours (e.g. increased physical activity and diet change). Results: The wellness service improved staff health for those with an 'at risk' health profile from baseline. These improvements were maintained in subsequent follow-up assessments. Improvement from baseline to 1-year follow-up was observed for all health indicators as was the maintenance of this improvement in years 2, 3 and 4. Conclusions: The service demonstrates that a university-based wellness service using a combination of motivational interviewing and health screening to elicit behaviour change (and subsequent improvements in health-related outcomes) was successful in improving the health of employees with an 'at risk' profile.